2021
DOI: 10.1016/j.envres.2021.111092
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of CO2 and aerosol (PM2.5, PM10, UFP) concentrations during the reopening of schools in the COVID-19 pandemic: The case of a metropolitan area in Central-Southern Spain

Abstract: Public health authorities have been paramount in guaranteeing that adequate fresh air ventilation is promoted in classrooms to avoid SARS-CoV-2 transmission in educational environments. In this work it was aimed to assess ventilation conditions (carbon dioxide, CO 2 ) and suspended particulate matter (PM 2.5 , PM 10 and UFP) levels in 19 classrooms – including preschool, primary and secondary education – located in the metropolitan area of Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 34 publications
4
41
1
3
Order By: Relevance
“…Similarly, the CO 2 mean levels observed in this study revealed to be lower than those documented for the European educational buildings in the cross-sectional European Union-funded HESE (Health Effects of School Environment) study and, more specifically, up to half of the mean values determined in 16 classrooms of 8 schools in Italy (Simoni et al, 2006, 2010 ); even if similar maximum values were found. On the other hand, according to Villanueva et al (2021) , the pre-school (classroom 2) was the educational environment showing the lowest mean and maximum values of CO 2 concentration probably due to the presence of seven transom windows always open (as reported in the questionnaires).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Similarly, the CO 2 mean levels observed in this study revealed to be lower than those documented for the European educational buildings in the cross-sectional European Union-funded HESE (Health Effects of School Environment) study and, more specifically, up to half of the mean values determined in 16 classrooms of 8 schools in Italy (Simoni et al, 2006, 2010 ); even if similar maximum values were found. On the other hand, according to Villanueva et al (2021) , the pre-school (classroom 2) was the educational environment showing the lowest mean and maximum values of CO 2 concentration probably due to the presence of seven transom windows always open (as reported in the questionnaires).…”
Section: Resultsmentioning
confidence: 89%
“…It's important to underline that during the first day, inside the classroom 6, 20 students and 1 teacher were present while inside the classroom 5, the total number of bystanders was 12 (11 students and 1 teacher). Anyway, other classrooms characterized by a high number of persons, for instance the classroom 4 (21) and 9 (19), showed CO 2 levels lower than those monitored in classroom 6 probably due to a more efficient ventilation strategy in terms of frequency and duration of windows and door opening as well as to hourly cross-ventilation ( Villanueva et al, 2021 ) ( Fig. 2 and Table 2 ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…A large part of energy consumption in Italy is caused by poor maintenance and renovation of school buildings [22]. In addition, the current pandemic of SARS-CoV-2 has highlighted numerous deficits in buildings and the need has emerged to adequately ventilate indoor spaces [23,24], especially schools that, unlike other non-residential buildings, had to remain open even at crucial times of the spread of the virus, despite their worst indoor environmental conditions [25]. Here, to the problem of overheating and, therefore, the need to increase the capacity of the cooling system, is added the need to further increase the loads through the installation of forced ventilation systems, worsening electricity demands.…”
Section: The Italian Building Stockmentioning
confidence: 99%